f(x)=x(x-1)(x-2)求导
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 14:11:41
f(x)=x(x-1)(x-2)求导f(x)=x(x-1)(x-2)求导f(x)=x(x-1)(x-2)求导f(x)=x^3-3x^2+2x导数为3x^2-6x+2f(x)=x(x^2-3x+2)=x
f(x)=x(x-1)(x-2)求导
f(x)=x(x-1)(x-2)求导
f(x)=x(x-1)(x-2)求导
f(x)=x^3-3x^2+2x
导数为3x^2-6x+2
f(x)=x(x^2-3x+2)=x^3-3x^2+2x
导数f'(x)=3x^2-6x+2
3x²-6x+2
f(x)=x^2+1求导
f(x)=(1+x)/(2)求导,
f(x)=x(x-1)(x-2)求导
f(x)=(x-1)(x-2).(x-3)求导
f(x)=(x-1)(x-2).(x-2008)求导
f(x)=x^2x 求导
f(x)=(2x+1)(x-1)求导
f(x)=1/2(x-1/x)-lnx求导
f(x)=(x-1)^2(x+1)^3 求导
f(x)=2x/x^2+1求导
f(x)=ln(x+√1+x^2) 求导
f(x)=x+2√(1-x) 求导
f(x)=a^(x+1)求导,
f(x)=2x+3求导
求导f(x)=xe^(-x^2)
f(x)=x(x+1) (x+2)****(x+n),求f(0)求导,
f(x)=e^x/(x-1)对x求导
f(1/x)=x,f(x)求导,